Assembling past worlds - Harris, Oliver J. T., author.
1 online resource
Keywords: "Assembling Past Worlds draws on new materialism and the philosophy of Gilles Deleuze to explore the potential for a posthumanist archaeology. Through specific empirical study, this book provides a detailed analysis of Neolithic Britain, a critical moment in the emergence of new ways of living, new relationships between materials, people, and new forms of architecture. It achieves two things. First it identifies the major challenges that archaeology faces in the light of current theoretical shifts. New ideas place new demands on how we write and think about the past, sometimes in ways that can seem contradictory. This volume identifies seven major challenges that have emerged, and sets out why they matter, why archaeology needs to engage with them, and how they can be dealt with through an innovative theoretical approach. Second, this volume explores how this approach meets these challenges through an in-depth study of Neolithic Britain. It provides an insightful diagnosis of the issues posed by current archaeological thought and is the first volume to apply the philosophy of Gilles Deleuze to the extended analysis of a single period. Assembling Past Worlds will show how new approaches are transforming our understandings of past worlds, and in so doing, how we can meet the challenges facing archaeology today. It will be of interest to both students and researchers in archaeological theory and the Neolithic of Europe"--